Peran Kepolisian Dalam Pelaksanaan Vaksinasi Di Kota Padang Sidempuan - Nasution, Nurul Annisyah; Harahap, Ikhwanuddin; Kurniawan, Puji (Jurnal El-Thawalib, 2024)
This study aims to determine the role of the Indonesian National Police in implementing the Regulation of the Minister of Health of the Republic of Indonesia Number 10 of 2021 concerning Implementation of Vaccinations in the Context of Mitigating the Covid-19 Pandemic in the City of Padang Sidempuan. This researcher is a field research (Field Research) with a qualitative approach. The primary data sources in this study were the Padang Sidempuan City Police, Padang Sidempuan City Health Office employees, several local residents and secondary data sources were books, laws, articles and several journals. The data collection techniques for this research are observation, interviews and documentation which will then be analyzed using descriptive qualitative analysis techniques. The results of this study indicate that the Police have played an active role in inviting, encouraging and socializing the implementation of vaccinations and increasing public awareness about vaccines so that people are not affected by vaccine issues that are not true. Factors that influence the implementation of vaccinations in the City of Padang sidempuan, namely there are inhibiting factors that the community is still little educated about vaccines and lack of awareness about the importance of health and supporting factors, namely Krepolisian in collaboration with other agencies or institutions such as the Health Service. As for the fiqh siyasa review of the role of the Police in implementing the regulation of the Minister of Health of the Republic of Indonesia that the police are officers who carry out the tasks given by the leader, which in fiqh siyasa this leader is called ulil amri and in the fiqh siyasah rules it states that "Tasroful imamu a'larroiyyati manuwtun bil maslahati" which means, the policy of an imam or government must be based on benefit. So, if the role of the police is related to fiqh siyasa, there will be no deviations so that it does not harm the local community in carrying out the vaccination.